2010
DOI: 10.1007/s00024-010-0228-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Tectonic and Landslide-Generated Tsunami Runup at Seward, Alaska During the M W 9.2 1964 Earthquake

Abstract: We apply a recently developed and validated numerical model of tsunami propagation and runup to study the inundation of Resurrection Bay and the town of Seward by the 1964 Alaska tsunami. Seward was hit by both tectonic and landslide-generated tsunami waves during the M W 9.2 1964 megathrust earthquake. The earthquake triggered a series of submarine mass failures around the fjord, which resulted in landsliding of part of the coastline into the water, along with the loss of the port facilities. These submarine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…We interpret this growth fold to represent the along‐strike expression of the Bainbridge fault, a fault that parallels and is possibly related to the Contact fault system (Figure ) [ Helwig and Emmet , 1981; Dumoulin , ; Bol and Gibbons , ; Wilson and Hults , ]. Along the Junken Trough profile, this fold is likely rooted in a fault at depth, and a large seafloor scarp suggests this fault may pose a significant tsunami or ground‐shaking hazard to adjacent mainland communities and infrastructure, including Seward and other shallow waterways along the southern Kenai Peninsula [e.g., Plafker , 1969; Suleimani et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We interpret this growth fold to represent the along‐strike expression of the Bainbridge fault, a fault that parallels and is possibly related to the Contact fault system (Figure ) [ Helwig and Emmet , 1981; Dumoulin , ; Bol and Gibbons , ; Wilson and Hults , ]. Along the Junken Trough profile, this fold is likely rooted in a fault at depth, and a large seafloor scarp suggests this fault may pose a significant tsunami or ground‐shaking hazard to adjacent mainland communities and infrastructure, including Seward and other shallow waterways along the southern Kenai Peninsula [e.g., Plafker , 1969; Suleimani et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Splay faults that extend across the western Gulf of Alaska shelf are consistent with the Plafker [] observations and the Suleimani et al . [] tsunami model, which showed that a source on the continental shelf is needed to produce the tsunami that arrived at Seward about 30 min after the earthquake. Plafker [] recognized that faults must have ruptured in the Gulf of Alaska during the 1964 earthquake to produce the footwall uplift along the south shore of Montague Island and to account for additional tsunami runups along the Kenai Peninsula; however, these hypothesized faults or fault extensions have not been identified.…”
Section: The Mw 92 1964 Earthquake and Related Upliftmentioning
confidence: 99%
“…They have been successfully correlated to historical earthquakes and were used to identify prehistorical events. Especially in fjords or bays, mass movements can be catastrophic (Syvitski and Schafer, 1996;Bøe et al, 2000;Urgeles et al, 2002) and potentially induce tsunamis (Tocher and Miller, 1959;Ward, 2001;L'Heureux et al, 2011;Suleimani et al, 2011). These, in turn, represent great hazards for coastal villages and harbors, which in many cases provide the best access to remote inland areas.…”
Section: Introductionmentioning
confidence: 97%
“…[] are able to reproduce observed runup at Valdez old town with a far‐traveled debris flow model. Here we investigate whether the simplest landslide scenarios can explain the observations; establishing the range of possible model fits is useful since quantitative landslide tsunami forecasts are becoming more prevalent [e.g., Masson et al ., ; ten Brink et al ., ; Suleimani et al ., ; Nicolsky et al ., ].…”
Section: Observationsmentioning
confidence: 99%